OVERCOMING SPEAKING ANXIETY AMONG TERTIARY EFL STUDENTS THROUGH THE ED-SHARING PROGRAM - Anissatusholihah; Shafa Salsabila; Octa Aulia Rindang Raharja (2025)
Speaking English effectively is essential at all educational levels, particularly given that it is a universal language that is employed in a wide range of professional and educational settings. Nevertheless, considering the significance of it, overcoming speaking anxiety remains an essential challenge for many students, hindering the opportunity to speak English with confidence. The aim of this research project is to investigate the points of view and experiences of Central Java university students who took part in the Ed-Sharing program, which aims at assisting students in managing and overcoming their fear of speaking publicly. Applying a descriptive qualitative methodology, this research collects data by conducting in-depth interviews with 7 individuals who actively participated in the Ed-Sharing initiative. The findings revealed that lack of practice, limited knowledge and vocabulary, the fear of making a mistake and judgment sensitivity, and a sense of insecurity and nervousness were the main causes of speaking anxiety. The results indicate that by providing a fun and interactive strategy and encouraging students to practice speaking in a secure environment, the Ed-Sharing program reduced anxiousness. The achievement of the program shows how crucial it is to build a setting that encourages practice and lessens the fear of being judged. The importance of organized, interactive programs for decreasing speaking anxiety along with improving English language proficiency is highlighted by this research.